Training for improved vertical jump - Kraemer, W. J.; Newton, R. U. (1994)
1. Vertical jump performance is determined by a complex interaction among several factors, including the maximal force that the involved musculature can develop, how fast that force can be developed, and the neural coordination of the movement. 2. A portion of the power developed during a vertical jump is derived from the stretch-shortening cycle that enhances muscular force by evoking the stretch reflex, and utilizes elastic energy stored in stretched tissues. 3. The vertical jump is a complex multi-joint movement that requires muscle coordination best improved by specific skill development. 4. Traditional strength training, explosive types of weight training, plyometrics, and Olympic lifting can be effective for increasing vertical jump. The form of training that is most effective is determined by the relative strengths and weaknesses of the athlete.